Challenges involved in multicultural education curriculum development - Susan San Htay; Hadiyanto Hadiyanto (Global Econedu, 2022)
In this article, you can observe challenges and considerations made by the educators, principals or curriculum developers while the multicultural education curriculum is being developed. The principals and educators of each school overcame by their own way from these challenges and develop the curriculum. Challenges empower to achieve our goals and make our lives move forward. Multicultural education curriculum is paramount, as it shapes them to be global citizens in democratic society which encourages building mutual understanding, tolerance and respect between groups.